Energy : crises, challenges and solutions - Singh, Pardeep; Singh, Suruchi, 1987-; Kumar, Gaurav, 1984-; Baweja, Pooja, 1977- (John Wiley & Sons, Inc., 2022)
"Addressing the energy crisis and climate change notions would entail dramatic policy changes in areas such as energy, global warming, and forest management. Energy and climate are also discussed together as the global economy was fuelled by fossil fuels, which could change the environment since the industrial revolution. This could lead to climate change that would be difficult and expensive to respond to. Fossil fuels play a significant role in the governance of economic growth, industrialization and human health. It is a fact that man's over-reliance on carbon trading is a huge mistake that could even lead to violent war between powerful nations and lead to political instability. The global energy system, therefore, calls for significant transformative steps to combat global climate change. If greenhouse gas emissions from fossil fuels burning continue unabated, a radical environmental transformation will be observed. Therefore, it is essential to direct efforts to support climate change goals at the national and global level in orthography policy"- Resumé vydavatele
Keywords: alternativní energetické zdroje; energetická politika; klimatické změny; alternative energy sources; energy policy; climate changes; elektronické knihy; kolektivní monografie; electronic books; collective monographs